Módulo de orientación magnética para captación de ángulos con capacidad de comunicación serial a datalogger e interfaz gráfica - Lino Borbor, Rodrigo Alberto (2010)
Robots, as well as air and sea transports, require positioning systems to know their location and direction. Considering that not all systems are fully reliable, the risk of occurring an accident -due to the failure of their positioning modules- is on the run. This project uses a compass prototype as an alternative method of directing to a route, which has a similar operation to an analogue compass, yet it contributes a digital output of orientation, with respect to the Earth's magnetic field. For handling the digital compass it is necessary the use of a microcontroller, which plays as the interface between the compass module and another device assigned to other applications requiring the direction input. The digital compass is going to be connected to a circuit, storing the collected data (datalogger), and also to another one, which displays samples taken with a graphical interface (GLCD). The mentioned circuits are not included into this project, however, they are going to be mentioned for the connections. In conclusion, this project looks for contributing with a system of digital support to the orientation.